Consistência do Roteiro para Avaliação de Riscos Músculo-Esqueléticos (RARME) em relação a avaliações de desconforto, esforço, afastamento do trabalho e análise ergonômica - Sato, Tatiana de Oliveira (2005)
Work-related musculoskeletal disorders (WMSDs) constitutes a group of disturbs, with multifactorial origin, mainly promoted by workplace factors (physical, organizational and psychosocial). WMSDs cause high human, social and economic costs, which justifies effort to determine more efficient prevention strategies. However, for an effective prevention is necessary to establish the main risk factors, and create or aprimorate assessment tools. It was proposed a new tool for risk assessment Checklist for musculoskeletal risk assessment (RARME). The objective of this study was to evaluate the consistency of this checklist in relation to other physical load indicators: discomfort and exertion ratings, sick leave and Ergonomic Workplace Analysis. Thirty-one subjects took part in this study. They performed fifteen different tasks involving repetitive motion pattern and manual material handling. Checklist was applied by direct observation in the workplace. No relation between the results from checklist and the other physical load indicators was identified. Several factors might have contributed to the lack of consistency between indicators. Exposure variability, cognitive overload of the observer, bias in observation methods, and instruments for risk measurement are important factors to be considered when analyzing the present results. Thus, although it was not possible to check the protocol validity, relevant methodological aspects when using theses types of checklists were discussed. Besides this, an improved version of RARME protocol is presented.